Development of keratin-based fibers fabricated by interfacial polyelectrolyte complexation for suture applications - Foo, Laura Li-En (2024)
Interfacial Polyelectrolyte Complexation (IPC) is a convenient way to produce composite, micro-scale fibers. In this paper, we report the successful development of novel keratin-based IPC fibers and also demonstrate the feasibility of using these fibers as sutures through a proof-of-concept in vivo study. Two composite fibers were produced: chitosan-keratin (CK) and keratin-keratin (KK). These fibers were evaluated for their physico-chemical, mechanical and biochemical properties. In the dry state, the CK fiber had a greater Young’s modulus of about 2 GPa while the KK fiber registered a longer strain-at-break of about 100% due to the strain-stiffening effect. Notably, the keratins were found to assemble into amyloids within the composite fibers based on Congo red staining and Wide-Angle X-Ray Scattering. Functionally, both fibers were malleable could be weaved, braided and knotted. When used as sutures to close incisional wounds in mice over 21 days, these fibers were found to elicit minimal host tissue response and were partially degraded over the duration. Interestingly, the KK fiber evoked a lower extent of immune cell response and fibrous capsule encapsulation that was comparable to commercial, non-absorbable Dafilon® sutures. This work demonstrated the possibility of producing keratin-based IPC fibers which may find practicality as medical sutures.